Evaluating the subjective benefit of hearing rehabilitation in adults with intellectual disability. (March 2013) - Coppens-Hofman, Marjolein C.; Koch, Henriëtte H.; Maassen, Ben A.M.; Snik, Ad F.M.
Abstract Objective: Subjective benefit of hearing aid fitting was assessed in adults with hearing loss and moderate intellectual disabilities who live in supported accommodation for people with intellectual disabilities. Hearing aids were bilaterally fitted in 37 hearing impaired adults. Study design: Subjective benefit was assessed six months after hearing aid fitting with the 'Glasgow Children's Benefit Inventory' questionnaire, which was completed by caregivers. Results: Questionnaire scores revealed good hearing aid use and variable, but relatively low, subjective benefit. Subjective benefit was absent or negative in one-third of the subjects. Conclusion: According to the caregivers, hearing aid fitting in hearing impaired adults with intellectual disability was only partially beneficial. As the mode of communication is often basic in assisted living environment, caregivers may be unaware of any hearing problems.